The translator’s voice through the translation of characters’ names in Bian Cheng - Guo, Xiaohui; Ang, Lay Hoon; Sabariah Md Rashid,; Ser, Wue Hiong (Penerbit Universiti Kebangsaan Malaysia, 2020)
Bian Cheng is a representative novel of Modern Chinese Literature. One of the most translated works of Modern Chinese Literature, the novel demonstrates diversified folklore, which is fully embedded and embodied in the images presented by the names of its characters. This qualitative study compares the images of names in the original Chinese version and an English version translated by Kinkley in an attempt to reveal how translator’s voice is reflected by varying translation techniques. Newmark’s model of translation techniques and MillánVarela’s model of translator’s voice are employed for the nuanced analysis. The investigation uncovers two major translation techniques in this regard: amplification and reproduction. The former, which shows a stronger translator’s voice, is used more frequently than the latter, which displays a relatively weaker translator’s voice. The study also shows that the strong translator’s voice does not necessarily convey the corresponding and equivalent image, and the weak one fails to do so even at a less satisfactory level. It is thus concluded that complicated source culture should be paid sufficient and accurate attention through the proper articulation of translator’s voice so that the equivalent and similar images could be successfully presented and communicated through translation.